Pemberdayaan Masyarakat dalam Program Quran Qorner - M Iqbal Arrosyad; Fandi Nugroho; Adi Saputra (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
Society is currently starting to decline in the practice of the Quran, especially in the Pangkalbalam hamlet. This is evidenced by the low number of TPA students from year to year. This community empowerment activity is carried out with the stages of planning, implementation, and evaluation. The results showed that the activity was carried out for 4 days at Shiyaul Haq TPA with teaching by the service team and participants from children in Pangkalbalam Village, the material presented included basic reading of the Quran, Tartil, Tajwid, and Recitation. The advantages of this activity are that it really helps the running of Al-Quran learning activities at the TPA, the material presented can be absorbed and practiced, and the activities run smoothly until the end of the activity. While the drawbacks, there are still students who arrive late, there is noise or students are chatting with their sidekick typing the delivery of material, and there are still those who have not had time to recite the Quran because the time that is carried out is still lacking.